2021
DOI: 10.1097/prs.0000000000008013
|View full text |Cite
|
Sign up to set email alerts
|

Prepectoral versus Subpectoral Tissue Expander Breast Reconstruction: A Historically Controlled, Propensity Score–Matched Comparison of Perioperative Outcomes

Abstract: Background:The rising popularity of prepectoral tissue expander placement with acellular dermal matrices in immediate breast reconstruction has prompted many studies on the safety of this technique. However, a comprehensive propensity-matched, historically controlled trial comparing perioperative outcomes following prepectoral versus partial subpectoral (dual-plane) placement of tissue expanders is lacking. Methods: Retrospective propensity-matched cohort analysis was performed on all patients of two senior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Its advantages include the elimination of animation deformities and muscle spasms. Studies have also shown that it is associated with less pain, is time-saving, and provides excellent aesthetic outcomes ( 46 - 48 ). Candidates for prepectoral breast reconstruction should have well-vascularized skin flaps and sufficient fat depots for fat grafting based on the concept of a bioengineered breast ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its advantages include the elimination of animation deformities and muscle spasms. Studies have also shown that it is associated with less pain, is time-saving, and provides excellent aesthetic outcomes ( 46 - 48 ). Candidates for prepectoral breast reconstruction should have well-vascularized skin flaps and sufficient fat depots for fat grafting based on the concept of a bioengineered breast ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“… 58 , 59 Thus, these techniques cannot be assessed in this trial, and the results’ applicability to such techniques is uncertain. According to recent studies, 60 , 61 , 62 , 63 , 64 , 65 , 66 however, the prepectoral position (which, in principle, always includes some type of mesh) renders no higher SSI rates compared with the subpectoral position, so multiple-dose antibiotic prophylaxis is probably not indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported outcome scores are effective in determining patient satisfaction and quality of life, but it is also important to address postoperative complications. There is no consensus on whether prepectoral versus subpectoral placement is associated with more complications, but prepectoral has been associated with higher seroma rates [ 27 , 28 ]. Though our TE removal rates were higher than previously reported values, the complication rates in the prepectoral cohort of Haddock et al were similar to ours [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on whether prepectoral versus subpectoral placement is associated with more complications, but prepectoral has been associated with higher seroma rates [ 27 , 28 ]. Though our TE removal rates were higher than previously reported values, the complication rates in the prepectoral cohort of Haddock et al were similar to ours [ 28 ]. Though the current evidence suggests that certain patients can undergo reconstruction without ADM, longer term, prospective studies are needed for definitive answers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%